2017
DOI: 10.1080/14767058.2017.1301926
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression among women hospitalized due to threatened preterm labor in a high-risk pregnancy unit in Greece

Abstract: About one quarter of the pregnant women hospitalized in the HRPU due to threatened preterm labor were depressed based on the EPDS. Thoughts of abortion were associated with a sixfold increase in the risk of depression, while no associations were found between antenatal depression and other sociodemographic and obstetric parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 47 publications
5
36
0
4
Order By: Relevance
“…This might be explained that unplanned pregnancies are more likely to be unwanted, and unwanted pregnancies are the major causes of induced abortions which can cause many complications if not managed safely. Besides, an unplanned pregnancy can bring worries during pregnancy because women usually are not mentally ready to take care of the pregnancy in such circumstances [37]. Also, an unwanted pregnancy, especially during the premarital period has a negative attitude towards the current pregnancy [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained that unplanned pregnancies are more likely to be unwanted, and unwanted pregnancies are the major causes of induced abortions which can cause many complications if not managed safely. Besides, an unplanned pregnancy can bring worries during pregnancy because women usually are not mentally ready to take care of the pregnancy in such circumstances [37]. Also, an unwanted pregnancy, especially during the premarital period has a negative attitude towards the current pregnancy [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…A latest study in Spain had cited that children of patients who presented with threatened preterm labor in their pregnancy but delivered at term had increased risk of mild neurodevelopmental delay when compared to uncomplicated pregnancy children [17]. Another study conducted in Greece showed that 24.3% prevalence of antenatal depression (based on Edinburgh Postnatal depression scale) in women admitted for threatened preterm labor [18]. This imposes the importance of appropriate diagnosis in these women so that they do not suffer unnecessary stress due to hospitalization and improper diagnosis.…”
Section: Mini Reviewmentioning
confidence: 99%
“…Several predisposing factors for these disorders are known. High-risk pregnancy [14], history of prepregnancy psychological disorders [15], stressful events during pregnancy [16], and economic and social factors [17,18], are known risk factors. The importance of identifying women at risk of depression and anxiety during pregnancy has led screening programs to be included in many prenatal care programs in developed countries [19].…”
Section: Introductionmentioning
confidence: 99%